PENGARUH LAMANYA PENGGUNAAN KB SUNTIK DMPA TERHADAP PENINGKATAN KADAR GULA DARAH AKSEPTOR KB SUNTIK DI KOTA KUPANG - Kadek Dwi Ariesthi (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
In Kupang City in 2016, there were 45,625 acceptors of NonMKJP KB acceptors and 3,813 MKJP KB acceptors, with the highest choice of injecting KB using 42,820 (86.6%). This study aims to analyze the effect of the length of dmpa injection syringes on the increase in blood sugar levels of injection injector acceptors in Kupang city. Descriptive research with a survey method with a retrospective study was conducted from April to August 2019 in the working area of ​​Puskesmas throughout the City of Kupang. The sample is acceptors who have used KB injections for 3 months for more than two years, with a total of 200 acceptors. The data collected is secondary data and primary data. Data analysis was performed univariately and bivariately. The results showed that there was a relationship between the length of use of injection injections KBPA to increase blood sugar, this can be shown by the value of Sig. (2-tailed) 0.001 <0.05, and the correlation coefficient value is 0, 228 which means there is a relationship but it is weak.